The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cmtd.202100041
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Aqueous Phase Reactions by Operando ATR‐IR Spectroscopy at High Temperature and Pressure: A Biomass Conversion Showcase

Abstract: Spectroscopic insight into aqueous phase catalytic reactions under realistic conditions aids detailed understanding and fosters further improvements. However, this is also very challenging, particularly in the liquid phase, given the typically elevated temperatures and pressures employed. Here, we report an operando Attenuated Total Reflectance‐Infrared (ATR‐IR) spectroscopic method to monitor the Aqueous Phase Reforming (APR) of Kraft lignin at 225 °C and 30 bar over a Pt/Al2O3 catalyst. This is a showcase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Chemometric modelling and IR analyses of selected lignins has already been tested to gather information on their botanical origin, lignin content, linkage distributions, molecular weight parameters, sugar content and functional group contents. [13][14][15][16][17] Some studies reported a good performance of the models established and reasonably accurate prediction of specific parameters, such as S/G ratios, while others reported high relative errors and reduced accuracy for parameters such as dispersity in molecular weight (Ð M ), M w , or β-5 and β-β inter-unit abundancies. [18] Evidently, the quality of the evaluation model does not only depend on the chemometric approach and the significance of the data basis, but also on the quality of the reference values obtained by conventional analytical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemometric modelling and IR analyses of selected lignins has already been tested to gather information on their botanical origin, lignin content, linkage distributions, molecular weight parameters, sugar content and functional group contents. [13][14][15][16][17] Some studies reported a good performance of the models established and reasonably accurate prediction of specific parameters, such as S/G ratios, while others reported high relative errors and reduced accuracy for parameters such as dispersity in molecular weight (Ð M ), M w , or β-5 and β-β inter-unit abundancies. [18] Evidently, the quality of the evaluation model does not only depend on the chemometric approach and the significance of the data basis, but also on the quality of the reference values obtained by conventional analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chemometric modeling comes into play, being used to establish a reliable model for the prediction of the targeted properties. Chemometric modelling and IR analyses of selected lignins has already been tested to gather information on their botanical origin, lignin content, linkage distributions, molecular weight parameters, sugar content and functional group contents [13–17] . Some studies reported a good performance of the models established and reasonably accurate prediction of specific parameters, such as S/G ratios, while others reported high relative errors and reduced accuracy for parameters such as dispersity in molecular weight (Ð M ), M w , or β‐5 and β‐β inter‐unit abundancies [18] .…”
Section: Introductionmentioning
confidence: 99%
“…To do so, the operando ATR‐IR spectra were first corrected for background and temperature‐resolved solvent contributions using the temperature‐dependent single‐beam approach reported previously. [38] To this extent, the ATR‐IR spectra acquired in absorption mode were first converted to the corresponding single‐beam ATR‐IR spectra (Figure S2A), using the background spectrum of the empty ATR‐IR probe‐equipped reaction vessel under ambient conditions. The single‐beam operando ATR‐IR reaction spectra were then ratioed against the corresponding single‐beam spectra of the solvent measured at the identical temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported on an analytical protocol to deal with such challenges and to acquire high‐quality ATR‐IR spectra, for example, under APR reaction conditions. [38] Here, we now turn to the challenge of acquiring information on the M w from the ATR‐IR spectra by multivariate regression, using an ex‐situ SEC M w dataset to calibrate the operando spectroscopic method. Hence, a multivariate regression model was developed with the potential to replace off‐line SEC measurements with online operando spectroscopy measurements to monitor changes in the M w value of kraft lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with increasingly accessible advanced chemometrics analysis, this tool also has the potential to clarify complex reaction mechanisms that can lead the way to new routes for optimization. 54…”
Section: Discussionmentioning
confidence: 99%